PENGARUH KINERJA LINGKUNGAN TERHADAP CORPORATE FINANCIAL PERFORMANCE DENGAN CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE SEBAGAI VARIABEL INTERVENING - Riska Rusmaningsih; Iwan Setiadi (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
This study aims to analyze the effect of environmental performance on Corporate Financial Performance (CSP) with Corporate Social Responsibility Disclosure (CSRD) as an intervening variable. With the number of research samples as many as 60 samples who were determined by the purposive sampling method. Tests were carried out using the path analysis test. The results of this study indicate that environmental performance affects CFP, environmental performance affects CSRD, CSRD affects CFP, and environmental performance affects CFP without going through the CSRD.